Data table of animal bones found in Vatnsvik, lake Þingvallavatn, Iceland [Structured Data from Open Context] ... - Albína H Pálsdóttir (Zenodo, 2023)
This deposit archives structured-data files associated with the Data table of animal bones found in Vatnsvik, lake Þingvallavatn, Iceland Data Table resource published by Open Context. In general, Open Context is a dynamic and frequently updated database that integrates research data from a growing number of sources. However, Open Context also stores some static and unchanging, externally stored "Data Table" files. Unless otherwise indicated, the content of Data Table files (such as the resource deposited here) will not change even after updates to the Open Context database. Deposition File Overview This archival deposit includes two files, in two formats: CSV: The 144-data-table-of-animal-bones-found-in-vatnsvik-lake-thing.csv contains the tabular data content for this resource in a CSV format. JSON: The 144-data-table-of-animal-bones-found-in-vatnsvik-lake-thing.json provides additional metadata about the tabular data content for this resource in a JSON-LD format. Open Context is an open-source Python ...